The Course Improvement Flowchart: A description of a tool and process for the evaluation of university teaching - Morgan, P. (Journal of University Teaching and Learning Practice, 2008)
The use of evaluation to examine and improve the quality of teaching and courses is now acomponent of most universities. However, despite the various methods and opportunities forevaluation, a lack of understanding of the processes, measures and value are some of themajor impediments to effective evaluation. Evaluation requires an understanding of what toevaluate, how to evaluate it, how to collect and analyse the information and how to action andimplement what has been learned. The aim of this paper is to describe an instrument todocument not only the evaluative process, but also evaluative outcomes. The CourseImprovement Flowchart (CIF) provides a template for the application of an action inquiryframework. Throughout this process, the CIF template can be used to document keyrecommendations emanating from multiple sources of feedback so that a proactive statement ofintent or action plan for teaching and course improvement is written. The resultantimprovements that may be achieved in teaching and course quality may lead to more satisfyingteaching experiences, improved student outcomes and heightened professional growth as ateacher.